2023
DOI: 10.3390/ijms24032888
|View full text |Cite
|
Sign up to set email alerts
|

Longevity, Centenarians and Modified Cellular Proteodynamics

Abstract: We have shown before that at least one intracellular proteolytic system seems to be at least as abundant in the peripheral blood lymphocytes of centenarians as in the same cells of young individuals (with the cells of the elderly population showing a significant dip compared to both young and centenarian cohorts). Despite scarce published data, in this review, we tried to answer the question how do different types of cells of longevous people—nonagenarians to (semi)supercentenarians—maintain the quality and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 156 publications
0
4
0
Order By: Relevance
“…Additionally, as will be discussed below, they may have a genetic and epigenetic background that protects them from hyperstimulation. Proteodynamics, defined as the process of regulating the synthesis, modification, and elimination of proteins at the cellular level [ 46 ] is based on an efficient and self-regulated proteostasis signature, which delays or avoids proteostenosis and the establishment of a geroproteome based on proteins with deficient functionality, mutated, leading to the accumulation of residues resistant to proteolytic systems. This implies that, compared to the elderly, centenarians have a more effective DNA maintenance capacity, better transcriptional fidelity, translation with lower error frequency, and a better response to post-translational modifications and autophagy [ 46 ].…”
Section: Immunosenescence and Inflammaging In The Aging Process: Immu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, as will be discussed below, they may have a genetic and epigenetic background that protects them from hyperstimulation. Proteodynamics, defined as the process of regulating the synthesis, modification, and elimination of proteins at the cellular level [ 46 ] is based on an efficient and self-regulated proteostasis signature, which delays or avoids proteostenosis and the establishment of a geroproteome based on proteins with deficient functionality, mutated, leading to the accumulation of residues resistant to proteolytic systems. This implies that, compared to the elderly, centenarians have a more effective DNA maintenance capacity, better transcriptional fidelity, translation with lower error frequency, and a better response to post-translational modifications and autophagy [ 46 ].…”
Section: Immunosenescence and Inflammaging In The Aging Process: Immu...mentioning
confidence: 99%
“… Proteodynamics, defined as the process of regulating the synthesis, modification, and elimination of proteins at the cellular level [ 46 ] is based on an efficient and self-regulated proteostasis signature, which delays or avoids proteostenosis and the establishment of a geroproteome based on proteins with deficient functionality, mutated, leading to the accumulation of residues resistant to proteolytic systems. This implies that, compared to the elderly, centenarians have a more effective DNA maintenance capacity, better transcriptional fidelity, translation with lower error frequency, and a better response to post-translational modifications and autophagy [ 46 ]. In this way, a better cellular and molecular response to stressors would be maintained, avoiding injurious mechanisms to tissues and organs, and delaying oxidation, dysfunction, and cellular aging ( Fig.…”
Section: Immunosenescence and Inflammaging In The Aging Process: Immu...mentioning
confidence: 99%
“… 28 These studies would aid in understanding precisely how modifiable and nonmodifiable factors impact the organic evolution of centenarians. Cellular senescence, epigenetic clocks, and alterations in stem cells, 29 are some of the cellular and molecular processes that could theoretically reflect cellular proteodynamics, 30 adaptation to aging, 31 and the development of health phenotypes and prognosis during longevity. 32 Having specific data on these mechanisms could facilitate the identification of aging biomarkers for cells, tissues, organs, or diseases, 33 and predict the onset of age‐related chronic diseases.…”
Section: The Importance Of Studying Aging and Centenariansmentioning
confidence: 99%
“…The primary objective of the review authored by Frankowska et al [17], and published in this S.I., was to explore the role of proteins in the context of longevity. The authors had previously demonstrated the intriguing observation that at least one intracellular proteolytic system exhibited comparable abundance in the peripheral blood lymphocytes of centenarians as that in the same cell type of young individuals [18].…”
Section: Proteodynamicsmentioning
confidence: 99%